Вплив логістичних провайдерів на розвиток регіональної економіки - Оксенюк, Катерина Ігорівна (Луцьк : ЛНТУ, 2024)
У статті досліджено вплив логістичних провайдерів на розвиток регіональної економіки. Здійснено аналіз викликів, з якими стикаються логістичні провайдери, а також можливостей, які вони пропонують для забезпечення ефективності та конкурентоспроможності регіональних ринків.Удосконалено підхід до класифікації логістичних провайдерів за рядом ознак: рівнем послуг (3PL, 4PL, 5PL);географічним охопленням (локальні, регіональні, міжнародні провайдери); сферою діяльності (загальний логістичний провайдер; спеціалізований логістичний провайдер).Досліджено вплив логістичних послуг на розвиток бізнесу та стабільність регіональної економіки. Запропоновано напрями розвитку логістичних провайдерів: розвиток мультимодальних перевезень; впровадженняінноваційнихтехнологій;співпрацязміжнароднимилогістичнимикомпаніями;зростання електронної комерції; підвищення якості обслуговування

The article examines the influence of logistics providers in the development of the regional economy. The meaning of the term “logistics provider” is scientifically substantiated. It is established that such companies act as an intermediary between the producer and the consumer, ensuring the optimal flow of goods and services, increasing the efficiency of supply chain management. The routes and technologies used by logistics providers affect the speed, quality and cost of transporting goods, allowing regions to attract increase competitiveness. The approach to the classification of logistics providers has been improved according to a number of the following characteristics level of services (3PL, 4PL, 5PL); geographical coverage (local, regional, international); by field of activity (general logistics provider; specialized logistics provider). The main functions of logistics providers are substantiated: transportation, warehousing and cargo processing, order processing, inventory management etc. Logistics providers help reduce costs for transportation, storage, and other logistics processes, allowing businesses to focus on their core business. It has been proven that the effective activity of logistics providers directly affects the competitiveness of the region, attractiveness for investors and the quality of life of life of the population. Attention is paid to the challenges faced by providers (insufficient infrastructure development; regulatory barriers; shortage of qualified personnel; competition), as well as to the opportunities they offer to ensure the efficiency and competitiveness of regional markets. The mail opportunities for the development of logistics in the regions are: cooperation with state bodies; formation of logistics clusters; development of digital technologies; personnel training, etc. Logistics providers play a key role in the development of the regional economy. They contribute to increasing the availability of various goods and services for the residents of the region, which can have a positive effect on the development of business and raising the standard of living of the population. The effective activity of logistics providers directly affects: the growth of trade; investment attraction; creation of new jobs; strengthening economic ties between regions; improving the quality of life of the population etc.
The influence of logistics providers on the development of the regional economy
Keywords: провайдер; регіон; логістичний провайдер; логістична інфраструктура; логістична послуга